Molecular identification of morphologically similar microcercous cercariae of two trematode families, Paragonimidae and Troglotrematidae, concurrently found in the same snail species of the subfamily Triculinae - Doanh, Pham Ngoc; Van Hien, Hoang; Thi Dung, Bui (Folia parasitologica, 2020)
Microcercous cercariae possess a very short tail and are produced by digenean species of several families including medically important species, such as members of the genera Paragonimus Braun, 1899, Nanophyetus Chapin, 1927 and Troglotrema Odhner, 1914. During our survey of cercariae of Paragonimus spp. in Vietnam, we found microcercous cercariae from ten (0.29%) out of 3,400 snails of Triculinae gen. sp. 2. They were morphologically and molecularly analysed for species identification. The molecular analysis, based on ITS2 sequences, revealed two distinct species: four specimens were identical to Paragonimus proliferus Hsia et Chen, 1964 (Paragonimidae Dollfus, 1939), and the other six specimens were closest to members of the family Troglotrematidae Odhner, 1914 and were temporarily named Troglotrematidae gen. sp. Morphologically, cercariae of the two species found in this study are similar to each other in their gross characteristics but can be distinguished from one another by subtle morphological details. The cercaria of P. proliferus has an I-shaped excretory bladder and does not have mucous gland cells. In contrast, that of Troglotrematidae gen. sp. has a Y-shaped excretory bladder and mucous gland cells. Besides, the redia of P. proliferus is elongate with a short intestine and contains 5-6 cercariae whereas that of Troglotrematidae gen. sp. is more round with a longer intestine and harbours 3-4 cercariae. Our results have shown the importance of the shape of the excretory bladder and the presence/absence of mucous gland cells of the cercaria as well as the shape and size of the redia, and its intestinal length as valuable taxonomic characters of intramolluscan trematode larvae. In addition, the finding of similar microcercous cercariae of different species in the same snail species suggests that careful attention to morphological details is required in the differentiation of Paragonimus cercariae and those of closely related species.
Keywords: Animals; cerkárie; sekvenční analýza RNA; digenean larvae; Troglotrematidae; Cercaria; Vietnam; mezerníky ribozomální DNA; Paragonimus; DNA, Helminth; Phylogeny; Vietnam.; DNA helmintů; morphology; microcercariae; ITS2; DNA, Ribosomal Spacer; Snails; zvířata; fylogeneze; Sequence Analysis, RNA; hlemýždi